Non-photochemical Quenching Plays a Key Role in Light Acclimation of Rice Plants Differing in Leaf Color - Zhao, Xia; Chen, Tingting; Feng, Baohua; Zhang, Caixia; Peng, Shaobing; Zhang, Xiufu; Fu, Guanfu; Tao, Longxing (Frontiers in Plant Science, 2017)
Non-photochemical quenching (NPQ) is an important photoprotective mechanism in rice; however, little is known regarding its role in the photosynthetic response of rice plants with differing in leaf color to different irradiances. In this study, 2 rice genotypes containing different chlorophyll contents, namely Zhefu802 (high chlorophyll) and Chl-8 (low chlorophyll), were subjected to moderate or high levels of light intensity at the 6-leaf stage. Chl-8 possessed a lower chlorophyll content and higher chlorophyll a:b ratio compared with Zhefu802, while Pn, Fv/Fm and ΦPSII contents were higher in Chl-8. Further results indicated that no significant differences were observed in the activities of Rubisco, Mg2+-ATPase, and Ca2+-ATPase between these genotypes. This suggested that no significant difference in the capacity for CO2 assimilation exists between Zhe802 and Chl-8. Additionally, no significant differences in stomatal limitation were observed between the genotypes. Interestingly, higher NPQ and energy quenching (qE), as well as lower photoinhibitory quenching (qI) and production of reactive oxygen species (ROS) was observed in Chl-8 compared with Zhefu802 under both moderate and high light treatments. This indicated that NPQ could improve photosynthesis in rice under both moderate and high light intensities, particularly the latter, whereby NPQ alleviates photodamage by reducing ROS production. Both zeaxanthin content and the expression of PsbS1 were associated with the induction of NPQ under moderate light, while only zeaxanthin was associated with NPQ induction under high light. In summary, NPQ could improve photosynthesis in rice under moderate light and alleviate photodamage under high light via a decrease in ROS generation.